2014
DOI: 10.4103/1947-2714.134371
|View full text |Cite
|
Sign up to set email alerts
|

Oral health in 4-6 years children with cleft lip/palate: A case control study

Abstract: Background:Oro-facial clefts are a major public health problem. Children with clefts rarely escape dental complications.Aims:This study was to determine differences in the dental caries experience, gingival health, and prevalence malocclusion, enamel defects and oral mucosal lesions among 4-6 year old children with and without cleft in Panchkula.Materials and Methods:The sampling frame consisted of 4-6 year old children with clefts visiting Swami Devi Dyal Hospital and Dental College, Panchkula, India. As a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(83 citation statements)
references
References 10 publications
0
72
0
11
Order By: Relevance
“…Thus, the null hypothesis was rejected. The fact that the oral hygiene may be jeopardized and impaired in CL(P)-children has been suggested in many previous studies [2, 5, 8]. This can be a result of fear of brushing around the cleft area, the anatomy of the cleft or a loss of elasticity of the surgically repaired lip [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the null hypothesis was rejected. The fact that the oral hygiene may be jeopardized and impaired in CL(P)-children has been suggested in many previous studies [2, 5, 8]. This can be a result of fear of brushing around the cleft area, the anatomy of the cleft or a loss of elasticity of the surgically repaired lip [2].…”
Section: Discussionmentioning
confidence: 99%
“…The association between CL(P) and dental caries in children is not fully clear but a number of studies indicate a higher caries prevalence in children with different oral clefts in comparison with non-cleft controls [2–6]. Several factors can contribute to this higher susceptibility such as impaired oral hygiene [2, 5, 7, 8], enamel hypoplasia [9, 10] and early colonization of caries-associated microorganisms [11]. Furthermore, parents to children with CL(P) tend to overindulge the children and offer them sucrose-containing food and snacks as a compensation for their medical condition [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies from different parts of the world have shown a higher prevalence of dental caries in children with CL/P in comparison with non-cleft controls (Bokhout, Hofman et al 1996, Hewson, McNamara et al 2001, Kirchberg, Treide et al 2004, Al-Wahadni, Alhaija et al 2005, Stec-Slonicz, Szczepanska et al 2007, Al-Dajani 2009, Zhu, Xiao et al 2010, Chopra, Lakhanpal et al 2014. However, conflicting results have been reported including comprehensive reviews (Paul and Brandt 1998, Lucas, Gupta et al 2000, Lages, Marcos et al 2004, Hasslöf and Twetman 2007, Jindal, McMeans et al 2011, Antonarakis, Palaska et al 2013).…”
Section: Dental Caries Prevalencementioning
confidence: 86%
“…The background variables that differed between the two study groups were oral hygiene and salivary lactobacilli counts. The fact that oral hygiene may be jeopardized and impaired in children with CL/P has been suggested in many previous studies (Dahllöf, Ussisoo-Joandi et al 1989, Wong and King 1998, Chopra, Lakhanpal et al 2014. This can be a result of fear of brushing around the cleft area, the anatomy of the cleft or a loss of elasticity in the surgically repaired lip (Dahllöf, Ussisoo-Joandi et al 1989).…”
Section: Dental Caries Riskmentioning
confidence: 98%
See 1 more Smart Citation